2019
DOI: 10.3389/feart.2019.00337
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Atmosphere—Cryosphere Interaction in the Arctic, at High Latitudes and Mountains With Focus on Transport, Deposition, and Effects of Dust, Black Carbon, and Other Aerosols

Abstract: Editorial on the Research Topic Atmosphere-Cryosphere Interaction in the Arctic, at High Latitudes and Mountains With Focus on Transport, Deposition, and Effects of Dust, Black Carbon, and Other Aerosols Atmosphere and cryosphere are closely linked and therefore need to be investigated as an interdisciplinary subject. Most of the cryospheric areas have undergone severe changes in recent decades, while such areas have been more fragile and less adaptable to global climate change (Boy et al., 2019). Atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It also affects the radiation budget indirectly by altering cloud properties: dust can act as cloud condensation nuclei (CCN) and it is an important icenucleating particle (INP) type in the Arctic, with high relevance for mixed-phase cloud formation (Prenni et al, 2009;Morrison et al, 2012;Costa et al, 2017;Schepanski, 2018;Tobo et al, 2019;Si et al, 2019;Sanchez-Marroquin et al, 2020). Once deposited on snow or ice, dust reduces the surface albedo, thereby contributing to the melting of ice and snow during the sunlit part of the year (Bond et al, 2013;Kylling et al, 2018;Dagsson-Waldhauserova and Meinander, 2019;Gunnarsson et al, 2021). Furthermore, dust influences the carbon cycle as it fertilizes oceans and enhances biological productivity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It also affects the radiation budget indirectly by altering cloud properties: dust can act as cloud condensation nuclei (CCN) and it is an important icenucleating particle (INP) type in the Arctic, with high relevance for mixed-phase cloud formation (Prenni et al, 2009;Morrison et al, 2012;Costa et al, 2017;Schepanski, 2018;Tobo et al, 2019;Si et al, 2019;Sanchez-Marroquin et al, 2020). Once deposited on snow or ice, dust reduces the surface albedo, thereby contributing to the melting of ice and snow during the sunlit part of the year (Bond et al, 2013;Kylling et al, 2018;Dagsson-Waldhauserova and Meinander, 2019;Gunnarsson et al, 2021). Furthermore, dust influences the carbon cycle as it fertilizes oceans and enhances biological productivity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a high amount of bioavailable iron in suspended dust can have a major effect on high-latitude oceanic biogeochemical cycles and productivity 21 , 30 34 , and hence on the carbon cycle. Dark, basaltic dust particles from Iceland significantly decrease the albedo of snow- and ice-covered regions 24 , 35 – 38 . As a fundamental nutrient source for algae in ice, dust can enhance ice melting 39 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic is known to be warming faster than the rest of the world in response to changes in greenhouse gases, aerosols, and other climate drivers, a process called Arctic amplification [1]. It has been suggested that mineral dust contributes to Arctic amplification [2][3][4]. In particular light-absorbing particulate deposited on snow can reduce surface albedo and enhance the melting of snow and ice.…”
Section: Introductionmentioning
confidence: 99%